The Relationship Between Reading Culture and Learning Motivation in Yogyakarta - Nolita Arpan Lamba; Kartika Nur Fathiyah; Ahmad Chandra Jaya (Yayasan Keluarga Guru Mandiri, 2024)
Background reading culture is among the elements that encourage pupils to learn more motivation. Reading culture encourages individuals to seek knowledge, increase understanding, and broaden their horizons through various reading sources. The purpose of this study is to examine the connections between reading culture and student learning motivation to gather empirical data or facts about these relationships. This research methodology employs a correlational study design and a quantitative approach. Eighty students comprise the study's sample because the data distribution is near the normal curve. A positive correlation of 0.851 indicated a significant association in the data. According to the results, there is a strong and positive correlation between student learning motivation and reading culture. The research contributes to understanding how literacy practices can drive learning engagement, offering valuable insights for educators, policymakers, and parents to design more effective literacy programs to improve student motivation and educational outcomes in the region.